2005
DOI: 10.1007/s11182-005-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Triple Phosphides MgSiP2, ZnSiP2, and CdSiP2

Abstract: 537.226Pseudopotential calculations of the electronic structure of the compounds are performed to an approximation of the density functional theory within the basis of localized orbitals. The band structure and total and projected state density are calculated, and a complete interpretation of the x-ray spectra is given.Kemerovo State University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Further, MgSiP 2 is comprised of a tetragonal chalcopyrite structure, which is similar to the triple diamond‐derived structure, and this is dynamically stable 7 . In the last decade, MgSiP 2 has been explored extensively due to its wide and direct bandgap nature 7–13 . Basalaev et al 9 have performed the pseudopotential calculation to determine the electronic structure of ASiP 2 (A═Mg, Zn, Cd) compounds using density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…Further, MgSiP 2 is comprised of a tetragonal chalcopyrite structure, which is similar to the triple diamond‐derived structure, and this is dynamically stable 7 . In the last decade, MgSiP 2 has been explored extensively due to its wide and direct bandgap nature 7–13 . Basalaev et al 9 have performed the pseudopotential calculation to determine the electronic structure of ASiP 2 (A═Mg, Zn, Cd) compounds using density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…They can, however, be plagued by defect related absorption losses near the band edge when grown from the melt, but these can often be eliminated by post-growth processing. CdSiP 2 is a II-IV-V 2 compound that has been examined by several authors starting in the late 1960s [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Borshchevskii et al [5] reported halogen assisted vapor transport growth of the compound as early as 1967, and Spring-Thorpe and Pamplin [4] reported growth from molten tin solution in 1968.…”
Section: Introductionmentioning
confidence: 99%
“…The birefringence of tiny 2 Â 2 Â 0.2 mm 3 CdSiP 2 crystals grown from a molten tin flux was measured by Itoh et al [2] and found to be À 0.045 at 840 nm. More recent studies examined the cathodoluminescence [11] and nuclear magnetic resonance (NMR) spectra [12] of small CdSiP 2 crystalline samples, and recent theoretical studies examined the calculated electronic band structure [13][14][15][16]. Crystals grown through either solution or halogen-assisted vapor transport were never of sufficient size or quality to create non-linear optical devices or to measure the ordinary and extraordinary refractive index of CdSiP 2 as a function of wavelength throughout its transparency range to determine if it could be phase matched.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations depict that with BeSnN 2 and BeGeN 2 , MnBe shows anti-ferromagnetism, whereas MnSn and MnGe show ferromagnetism [12]. Finally in one of the works,the band structures, equilibrium lattice inputs parameters and structural parameters, bulk moduli, and cohesive energies for chalcopyrite structure of BeCN 2 , MgCN 2 , BeSiN 2 , MgSiN 2 , and MgSiP 2 are calculated by the linear-muffin-tin-orbital method [13][14][15]. A theoretical study has been performed in one of the papers in which the FP-LAPW method has been adopted based on TB-mBJ approximations to investigate the chemical bond, structural aspect, electronic and optical features.…”
Section: Introductionmentioning
confidence: 95%